O casal e a distribui????o dos recursos financeiros em diferentes fases do ciclo de vida familiar - Cardoso, Luciana de Barros Silva Alves (2017)
The purpose of this paper is to understand how couples at different stages of the family life cycle organize themselves financially. This is a qualitative research. The instruments used were a sociodemographic questionnaire and a semi-structured interview script, applied in five couples, one without children, one with a small child, one with teenage children, one with adult children and one elderly couple, ). Through the study, it has been observed that there are different ways for couples to organize themselves financially and that information about money is transmitted through transgenerational inheritances. These messages shape the way couples create a picture of the meaning of money and how they manage their finances. Regarding the gender issue, there is an inequality in the way women and men use their financial resources and women's spending on personal use is disqualified when compared to men's personal spending. In this respect, it is possible to conclude that women have more difficulties in investing their income. Regarding the money communication, it is clear that this is a little discussed issue between couples, and there is also a certain imbalance of power between the spouses. It is concluded that there are different ways for couples to have their financial resources, however, there is no certain way of managing them. It is suggested that this management be clarified within the marital relationship, especially in the changes in stages of the family life cycle, since the phase changes in the family life cycle demand a reorganization and redistribution of financial resources.